The information about the negotiation process with paramilitary, the demobilization and the Law of Justice and Peace in three national newspapers - Seguro Flórez, Adriana María (Folios, revista de la Facultad de Comunicaciones y Filología, 2014)
This article presents some results of the research “Journalistic information treatment of three crucial moments about the negotiation process with the paramilitary – having as a reference the demobilization and the Justice and Peace Law in Colombia”published in the newspapers El Tiempo,El Espectador and El Colombiano. In the findings it is identified that the majority of the articles are unsigned, the most mentioned subject in the informative pieces is the Justice and Peace Law, the most used journalistic gender is the news, in the source origin the biggest percentages are in the testimonies and announcements, and finally, the most cited sources are the state institutions and it is important to highlight low information contrast.